Analysis Of Malay Language Interference In Learning Indonesian At SMK - Jumriati, Jumriati; Nurhadi, Nurhadi; Swatika Sari, Esti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
The location of Sebatik Barat on the Indonesia-Malaysia border greatly influences the lives of its people. The use of student language in learning at school is no exception. This study aims to explain the process of Malay language interference when learning Indonesian at SMK Negeri 1 Sebatik Barat. This research was conducted due to disturbances during the interaction of learning Indonesian, both between students and students, as well as students and teachers. This research uses descriptive qualitative method. The data used in this study are students' utterances in the form of sentence quotations which show Malay language interference in Indonesian language learning by students at SMK Negeri 1 Sebatik Barat. Based on data analysis, it was found that there were 4 interference factors: (1) being carried away by habits in the mother tongue, (2) insufficient vocabulary of the recipient language, (3) the need for synonyms, and (4) the bilingualism of the speech participants. From these 4 aspects, it can be concluded that the most dominating factor of distraction is the bilingualism of the speech participants.